2017
DOI: 10.21887/ijvsbt.v13i02.10046
|View full text |Cite
|
Sign up to set email alerts
|

Economic Traits and Production Performance of Nandanam Quail Reared at Different Cage Stocking Densities

Abstract: This study was carried out to assess the effect of different cage stocking densities on the production performance of Nandanam quail III reared up to 42 days. Three hundred day old Nandanam quail III were randomly assigned to 2.5 x 1.5 ft cages and distributed with 3 treatments (20, 25 and 30 quails per cage or 0.17, 0.14 and 0.11 sq. ft per quail, respectively) and 4 replicates. There were significant differences among treatments for bi-weekly body weight, feed consumption, feed conversion ratio and net profi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…The fundamental tool for maximising the productive potential of birds is by selection. Around the world, a variety of selection techniques have been in use, ranging from mass selection to complete pedigree selection ( Krishna et al, 2016 ; Narinç et al, 2016 ; Durmuş et al, 2017 ; Pandian et al, 2017 ) to improve the Japanese quails’ performance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The fundamental tool for maximising the productive potential of birds is by selection. Around the world, a variety of selection techniques have been in use, ranging from mass selection to complete pedigree selection ( Krishna et al, 2016 ; Narinç et al, 2016 ; Durmuş et al, 2017 ; Pandian et al, 2017 ) to improve the Japanese quails’ performance.…”
Section: Introductionmentioning
confidence: 99%
“…Quail farming is a growing industry in India, because of the relatively higher profit margins ( Pandian et al, 2017 ; Prabakaran and Ezhil Valavan, 2020 ). As there is a need to promote the growth of these birds through selection programmes, different production performances were utilized for the genetic selection in the four different lines (L1, L2, L3, and L4) of Japanese quail maintained at the Poultry Farm Complex of Department of Poultry Science, Veterinary College and Research Institute, Namakkal, Tamil Nadu, India for the production of parent breeders and the characteristics that are taken into account are body weight, growth rate and egg production.…”
Section: Introductionmentioning
confidence: 99%
“…[ 30 ] An animal study conducted on Japanese quail breeder hatching eggs demonstrated significantly reduced embryonic mortality and significantly high total and fertile hatchability performance in the PEMF treated group compared to the controls. [ 31 ] A case series showed that 2 out of 3 infertile patients with extremely thin endometrial lining and multiple failed in vitro fertilization (IVF) cycles, were able to get pregnant after IVF following the treatment with ozone and PEMF (by the use of the hyperthermic ozone & carbonic acid transdermal therapy (HOCATT) machine) that significantly improved the endometrial lining thickness (EMT). [ 32 ]…”
Section: Introductionmentioning
confidence: 99%